2022
DOI: 10.1007/s00264-022-05639-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of dual-mobility cup in primary total hip arthroplasties: an Italian regional register (RIPO) study on three thousand, seven hundred and ten cases

Abstract: Purpose The purpose of the study was to investigate the outcome of dual-mobility cup (DM) compared with a standard cup (SC) in primary total hip arthroplasty (THA) in the long-term follow-up based on a regional Italian joint registry (RIPO). Methods The Registry of Prosthetic Orthopaedic Implant (RIPO) was consulted, looking for all primary THAs implanted from 2000 to 2019. Three thousand seven hundred ten were dual-mobility cup (DM) total hip arthroplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Several in vivo studies reported that the head diameter utilized in DMC was typically smaller than 32 mm. 52,53 This head was designed to fit within a larger polyethylene hemisphere, typically from 38 to 54 mm in diameter. 52 The hemisphere was designed to articulate with a smooth metal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vivo studies reported that the head diameter utilized in DMC was typically smaller than 32 mm. 52,53 This head was designed to fit within a larger polyethylene hemisphere, typically from 38 to 54 mm in diameter. 52 The hemisphere was designed to articulate with a smooth metal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term studies of first-generation DM implants have demonstrated their effectiveness in reducing the risk of revision due to dislocation compared to standard prosthetic implants. Additionally, DM constructs (DMC) have shown positive outcomes in patients with spinopelvic stiffness and neurologic disorders, making them a valuable option in specific clinical scenarios[ 1 , 2 , 13 , 14 ].…”
Section: Advantagesmentioning
confidence: 99%
“…DM cups consist of three joints: The inner joint, the smaller one, between the femoral head and the polyethylene liner, the outer larger joint between the metal cup and the polyethylene liner, and the “virtual” third joint between the stem neck and the peripheral border of the liner[ 1 ].…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations